Urinary incontinence in women and depressive disorders - Ogórek-Tęcza, Beata; Pulit, Aneta (Nursing in the 21st Century, 2012)
URINARY INCONTINENCE IN WOMEN AND DEPRESSIVE DISORDERS Introduction. Urinary incontinence is a very inconvenient disease which, when left untreated or improperly cared may lead to secondary complications both of a somatic and psychological nature. The very nature of the disease and its duration favour the occurrence of depressive disorders. Aim. The aim of the study was to assess of the occurrence of a depressive syndrome in females suffering from incontinence. Material and methods. One hundred females suffering from incontinence were covered with the study. The study was conducted at the Gynecological Ward of the Józef Dietl Hospital in Krynica-Zdrój. Diagnostic poll method and assessment method were applied. The study tools included own-prepared questionnaire and Standarized Beck Depression Scale. Results. the most usual type of urinary incontinence was effort urinary incontinence. Depressive disorders occurred in the case of 64% of the study group. Females with urinary incontinence most often suffered from mild or moderate depression (63%). Emotions which were dominant in women suffering from urinary incontinence are shame (39%), anger (20%), depression (15%). Conclusions. the frequency of the occurrence of depressive disorder in females suffering from urinary incontinence increases with time and the duration of the disease. Psychological assistance in connection with urinary incontinence is usually not offered. As many as 41% of the studied group expect assistance form a psychologist. Medics are expected to support females suffering from urinal incontinence with necessary information and advice.